High-strength foam composite material and foam heat preservation box prepared from high-strength foam composite material

By combining high-performance raw materials such as polylactic acid, hollow ceramic microbeads, and plant fiber reinforced bodies, high-strength foam composite materials have been developed, solving the shortcomings of traditional foam materials in terms of strength and environmental protection, and achieving efficient and environmentally friendly insulation solutions .

CN119432030AInactive Publication Date: 2025-02-14TAICANG YINGLIE PACKAGING MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411689064.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional foam materials use harmful chemicals during production, which are difficult to degrade, and have shortcomings in strength and durability, which cannot meet the needs of certain specific fields.

Method used

By combining high-performance raw materials such as polylactic acid, hollow ceramic microbeads, plant fiber reinforced bodies, graphene, etc., a high-strength foam composite material was developed, and a foam insulation box with excellent comprehensive performance was prepared through an optimized preparation process.

Benefits of technology

It achieves high strength, low thermal conductivity and good thermal insulation effect, and is suitable for a variety of application scenarios such as cold chain logistics and food preservation, and has an environmentally friendly and efficient production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432030A_ABST
    Figure CN119432030A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength foam composite material and a foam insulation box prepared from the same. The composite material is prepared from polylactic acid, hollow ceramic microspheres, lignocellulose, graphene oxide, an azodiisobutyronitrile foaming agent, a titanate coupling agent, a pentaerythritol stearate lubricant and a 1076 antioxidant according to a specific proportion. The average molecular weight of the polylactic acid is 20000-30000, and the average diameter of the hollow ceramic microspheres is 50-100 [mu] m. The preparation process comprises the steps of raw material mixing, hollow ceramic microsphere adding, foaming agent adding, melt blending, foaming forming, cooling curing and aftertreatment. The foam heat preservation box made of the composite material has good heat preservation performance and mechanical strength and is suitable for the field of heat preservation packaging. The composite material has the advantages of being renewable, environmentally friendly, high in strength, light and the like, the preparation method is simple, the production cost is low, and the composite material has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermal insulation materials, and specifically discloses a high-strength foam composite material and a foam thermal insulation box prepared from the same. Background Art

[0002] In the field of thermal insulation packaging, traditional foam materials such as polystyrene (EPS) and polyurethane (PU) are widely used due to their good thermal insulation effect. However, with the increasing awareness of environmental protection and the demand for sustainable development, the shortcomings of these traditional materials have gradually become prominent.

[0003] First, polystyrene and polyurethane foam materials often require the use of some environmentally harmful chemicals, such as foaming agents and catalysts, during the production process. These chemicals may release harmful gases during production and use, causing environmental pollution. In addition, during the waste treatment process after use, these materials are prone to long-term pollution of soil and water bodies due to their difficult-to-degrade characteristics, which is not in line with the green and environmental protection concept of modern society.

[0004] Secondly, traditional foam materials have obvious deficiencies in strength and durability. Especially when they need to withstand large external forces or are used for a long time, these materials are prone to breakage, deformation and other problems, which reduces their thermal insulation effect and service life. This not only increases the cost of replacement and maintenance, but also limits the application of these materials in certain specific fields.

[0005] In order to overcome these shortcomings of traditional foam materials, people began to explore new foam materials that are more environmentally friendly and high-strength. Polylactic acid, as a bio-based, degradable polymer material, has attracted much attention due to its good biocompatibility and degradability. However, pure polylactic acid foam materials still have certain limitations in terms of strength and lightness, and it is difficult to meet the needs of certain specific fields. Therefore, how to combine polylactic acid with other reinforcements and modifiers through reasonable formula design and preparation process to prepare new foam materials with excellent comprehensive performance has become a hot topic in current research. Summary of the invention

[0006] Based on the deficiencies in the prior art, the present invention discloses a high-strength foam composite material and a foam insulation box prepared therefrom.

[0007] The present invention includes the following technical solutions:

[0008] A high-strength foam composite material is made of the following raw materials: polylactic acid, hollow ceramic microspheres, plant fiber reinforcement, graphene, foaming agent, cross-linking agent, lubricant and antioxidant. By combining polylactic acid, hollow ceramic microspheres, plant fiber reinforcement (lignocellulose), graphene (graphene oxide) and other raw materials, the composite material exhibits high strength characteristics. The combined effect of these components improves the overall mechanical properties and structural stability of the material.

[0009] Furthermore, in the above-mentioned high-strength foam composite material, the average molecular weight of the polylactic acid is 20000-30000. As a bio-based material, polylactic acid has good biodegradability and reduces environmental pollution. At the same time, wood cellulose as a plant fiber reinforcement also increases the renewability and environmental protection of the material.

[0010] Furthermore, in the above-mentioned high-strength foam composite material, the hollow ceramic microspheres have an average diameter of 50-100 μm. Since hollow ceramic microspheres are used as filling materials, these microspheres can form a heat insulation layer in the material, effectively reducing heat transfer, thereby improving thermal insulation performance.

[0011] Furthermore, in the above-mentioned high-strength foam composite material, the plant fiber reinforcement is wood cellulose.

[0012] Furthermore, in the above-mentioned high-strength foam composite material, the graphene is graphene oxide.

[0013] Furthermore, in the above-mentioned high-strength foam composite material, the foaming agent is azobisisobutyronitrile.

[0014] Furthermore, in the above-mentioned high-strength foam composite material, the cross-linking agent is a titanate coupling agent, the lubricant is pentaerythritol stearate, and the antioxidant is 1076 antioxidant.

[0015] Furthermore, the above-mentioned high-strength foam composite material is made of the following raw materials, calculated by weight:

[0016]

[0017] The present invention also discloses a foam insulation box, which is prepared from the above-mentioned high-strength foam composite material, and comprises the following steps:

[0018] S1 raw material mixing: using a high-speed mixer with a stirring device to uniformly mix polylactic acid, cellulose, graphene oxide, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant according to the formula ratio;

[0019] S2: Add hollow ceramic microspheres to the uniformly mixed material, continue mixing, and control the stirring speed below 500 rpm until the microspheres are evenly distributed.

[0020] S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again;

[0021] S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending;

[0022] S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding;

[0023] S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material;

[0024] S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain the foam insulation box.

[0025] By precisely controlling the raw material ratio and preparation steps, such as using a high-speed mixer with a stirring device to mix the raw materials, controlling the stirring speed, the temperature of the melt blending and the conditions of the foaming molding, the uniformity and stability of the materials are ensured, and the production efficiency and product quality are improved.

[0026] The present invention also discloses the application of the composite material or foam insulation box in the field of insulation packaging. The foam insulation box prepared from the high-strength foam composite material has excellent insulation performance and environmental protection, and is suitable for packaging and storage of various products that require insulation, such as cold chain logistics, food preservation and other fields, and has broad market application prospects.

[0027] Compared with the prior art, the present invention has the following outstanding beneficial effects:

[0028] The present invention discloses a high-strength foam composite material and a foam insulation box prepared therefrom. By combining high-performance raw materials such as polylactic acid, hollow ceramic microbeads, lignocellulose, graphene oxide, and optimizing the preparation process, a high-strength and environmentally friendly foam composite material is successfully developed. It can be seen from the test examples that the thermal conductivity is as low as 0.030W / (m·K), the compression strength can reach 249Mpa, and the tensile strength reaches 0.32Mpa. The material not only has excellent mechanical properties and structural stability, but also shows good thermal insulation effects. Therefore, the foam insulation box prepared from this material is not only suitable for a variety of application scenarios such as cold chain logistics and food preservation, but also the production process is environmentally friendly and efficient, providing the market with a high-performance, sustainable insulation solution with broad application prospects and significant environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A process flow chart of a foam insulation box disclosed in the present invention;

[0030] Figure 2 Comparison of thermal conductivity (λ) W / (m·K) in the test cases;

[0031] Figure 3 Comparison of compressive strength (Mpa) in the test cases;

[0032] Figure 4 Comparison of tensile strength (Mpa) in the test cases. DETAILED DESCRIPTION

[0033] A high-strength foam composite material, calculated by weight, is made of the following raw materials:

[0034]

[0035] like Figure 1 As shown, a foam insulation box is prepared from the above-mentioned high-strength foam composite material, comprising the following steps:

[0036] S1 raw material mixing: using a high-speed mixer with a stirring device to uniformly mix polylactic acid, cellulose, graphene oxide, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant according to the formula ratio;

[0037] S2: Add hollow ceramic microspheres to the uniformly mixed material, continue mixing, and control the stirring speed below 500 rpm until the microspheres are evenly distributed.

[0038] S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again;

[0039] S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending;

[0040] S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding;

[0041] S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material;

[0042] S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain a foam insulation box.

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] A high-strength foam composite material, calculated by weight, is made of the following raw materials:

[0046]

[0047] A foam insulation box is prepared from the above-mentioned high-strength foam composite material, comprising the following steps:

[0048] S1 raw material mixing: using a high-speed mixer with a stirring device to uniformly mix polylactic acid, cellulose, graphene oxide, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant according to the formula ratio;

[0049] S2: Add hollow ceramic microspheres to the uniformly mixed material, continue mixing, and control the stirring speed below 500 rpm until the microspheres are evenly distributed.

[0050] S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again;

[0051] S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending;

[0052] S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding;

[0053] S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material;

[0054] S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain a foam insulation box.

[0055] Example 2

[0056] A high-strength foam composite material, calculated by weight, is made of the following raw materials:

[0057]

[0058] A foam insulation box is prepared from the above-mentioned high-strength foam composite material, comprising the following steps:

[0059] S1 raw material mixing: using a high-speed mixer with a stirring device to uniformly mix polylactic acid, cellulose, graphene oxide, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant according to the formula ratio;

[0060] S2: Add hollow ceramic microspheres to the uniformly mixed material, continue mixing, and control the stirring speed below 500 rpm until the microspheres are evenly distributed.

[0061] S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again;

[0062] S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending;

[0063] S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding;

[0064] S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material;

[0065] S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain the foam insulation box.

[0066] Example 3

[0067] A high-strength foam composite material, calculated by weight, is made of the following raw materials:

[0068]

[0069]

[0070] A foam insulation box is prepared from the above-mentioned high-strength foam composite material, comprising the following steps:

[0071] S1 raw material mixing: using a high-speed mixer with a stirring device to uniformly mix polylactic acid, cellulose, graphene oxide, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant according to the formula ratio;

[0072] S2: Add hollow ceramic microspheres to the uniformly mixed material, continue mixing, and control the stirring speed below 500 rpm until the microspheres are evenly distributed.

[0073] S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again;

[0074] S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending;

[0075] S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding;

[0076] S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material;

[0077] S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain the foam insulation box.

[0078] Comparative Example 1

[0079] A high-strength foam composite material, calculated by weight, is made of the following raw materials:

[0080]

[0081] A foam insulation box is prepared from the above-mentioned high-strength foam composite material, comprising the following steps:

[0082] S1 raw material mixing: using a high-speed mixer with a stirring device to uniformly mix polylactic acid, cellulose, graphene oxide, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant according to the formula ratio;

[0083] S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again;

[0084] S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending;

[0085] S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding;

[0086] S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material;

[0087] S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain the foam insulation box.

[0088] This comparative example does not contain hollow ceramic microspheres, and the rest is the same as Example 2.

[0089] Comparative Example 2

[0090] A high-strength foam composite material, calculated by weight, is made of the following raw materials:

[0091]

[0092] A foam insulation box is prepared from the above-mentioned high-strength foam composite material, comprising the following steps:

[0093] S1 raw material mixing: using a high-speed mixer with a stirring device to uniformly mix polylactic acid, graphene oxide, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant according to the formula ratio;

[0094] S2: Add hollow ceramic microspheres to the uniformly mixed material, continue mixing, and control the stirring speed below 500 rpm until the microspheres are evenly distributed.

[0095] S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again;

[0096] S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending;

[0097] S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding;

[0098] S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material;

[0099] S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain the foam insulation box.

[0100] This comparative example does not contain lignocellulose, and the rest is the same as Example 2.

[0101] Comparative Example 3

[0102] A high-strength foam composite material, calculated by weight, is made of the following raw materials:

[0103]

[0104] A foam insulation box is prepared from the above-mentioned high-strength foam composite material, comprising the following steps:

[0105] S1 raw material mixing: using a high-speed mixer with a stirring device to uniformly mix polylactic acid, wood cellulose, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant according to the formula ratio;

[0106] S2: Add hollow ceramic microspheres to the uniformly mixed material, continue mixing, and control the stirring speed below 500 rpm until the microspheres are evenly distributed.

[0107] S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again;

[0108] S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending;

[0109] S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding;

[0110] S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material;

[0111] S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain a foam insulation box.

[0112] This comparative example does not contain graphene oxide, and the rest is the same as Example 2.

[0113] Comparative Example 4

[0114] A high-strength foam composite material, calculated by weight, is made of the following raw materials:

[0115]

[0116]

[0117] A foam insulation box is prepared from the above-mentioned high-strength foam composite material, comprising the following steps:

[0118] S1: Mixing raw materials: Use a high-speed mixer with a stirring device to mix polylactic acid, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant evenly according to the formula ratio;

[0119] S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again;

[0120] S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending;

[0121] S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding;

[0122] S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material;

[0123] S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain a foam insulation box.

[0124] This comparative example does not contain hollow ceramic microspheres, cellulose and graphene oxide, and the rest is the same as Example 2.

[0125] Test Case

[0126] The materials in the upper foam insulation box in Examples 1-3 and Comparative Examples 1-4 were sampled and made into test blocks of 10 cm x 5 cm x 2 cm (thickness).

[0127] The following tests were conducted to test its thermal insulation performance and mechanical strength. The thermal insulation performance was measured by thermal conductivity (λ) in W / (m·K). The lower the thermal conductivity, the better the thermal insulation performance of the insulation material. The mechanical properties were tested by compressive strength (Mpa) and tensile strength (Mpa). Refer to GB / T 10801.1-2021 "Molded polystyrene foam (EPS) for thermal insulation"

[0128] The results are shown in Table 1 and Figure 2-4 shown.

[0129] Table 1 Thermal insulation material performance test

[0130]

[0131]

[0132] From the above data, it can be seen that the high-strength foam composite material disclosed in the present invention, by combining raw materials such as polylactic acid, hollow ceramic microspheres, plant fiber reinforcement (lignocellulose), graphene (graphene oxide), etc., the composite material exhibits high-strength characteristics. The combined effect of these components improves the overall mechanical properties and structural stability of the material, with a thermal conductivity as low as 0.030W / (m·K), a compression strength of 249Mpa, and a tensile strength of 0.32Mpa. It is not only suitable for a variety of application scenarios such as cold chain logistics and food preservation, but also has an environmentally friendly and efficient production process, providing the market with a high-performance, sustainable insulation solution with broad application prospects and significant environmental benefits.

[0133] The above are only a few preferred embodiments of the present invention, which are described in a more specific and detailed manner, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A high-strength foam composite material, characterized in that: It is made of the following raw materials: polylactic acid, hollow ceramic microspheres, plant fiber reinforcement, graphene, foaming agent, cross-linking agent, lubricant and antioxidant.

2. A high-strength foam composite material according to claim 1, characterized in that: The average molecular weight of the polylactic acid is 20,000-30,000.

3. The high-strength foam composite material according to claim 1, characterized in that: The hollow ceramic microspheres have an average diameter of 50-100 μm.

4. The high-strength foam composite material according to claim 1, characterized in that: The plant fiber reinforcement is wood cellulose.

5. The high-strength foam composite material according to claim 1, characterized in that: The graphene is graphene oxide.

6. The high-strength foam composite material according to claim 1, characterized in that: The foaming agent is azobisisobutyronitrile.

7. The high-strength foam composite material according to claim 1, characterized in that: The cross-linking agent is a titanate coupling agent, the lubricant is pentaerythritol stearate, and the antioxidant is 1076 antioxidant.

8. The high-strength foam composite material according to claim 1, characterized in that: Calculated by weight, it is made from the following raw materials: 100 parts of polylactic acid with an average molecular weight of 20,000-30,000 5-10 parts of hollow ceramic microspheres with an average diameter of 50-100 μm 15-30 parts of wood cellulose Graphene oxide 3-6 parts 2-4 parts of azobisisobutyronitrile foaming agent Titanate coupling agent 8-16 parts Pentaerythritol stearate lubricant 2-5 parts 1076 antioxidant 1-2 parts.

9. A foam insulation box, characterized in that: The high-strength foam composite material according to claim 8 is prepared, comprising the following steps: S1 raw material mixing: using a high-speed mixer with a stirring device to uniformly mix polylactic acid, cellulose, graphene oxide, titanate coupling agent, pentaerythritol stearate and 1076 antioxidant according to the formula ratio; S2: Add hollow ceramic microspheres to the uniformly mixed material, continue mixing, and control the stirring speed below 500 rpm until the microspheres are evenly distributed. S3: adding a foaming agent: adding azobisisobutyronitrile foaming agent to the mixed material, and mixing again; S4 melt blending: send the uniformly mixed materials into an internal mixer at a temperature of 120-140°C for melt blending; S5 Foaming molding: The melt-blended materials are fed into the insulation box mold for foaming molding; S6 Cooling and curing: After foaming, cool the mold to room temperature at a cooling rate of 2-4℃ / min to solidify the material; S7 post-processing: take out the solidified material from the mold, perform trimming, and obtain the foam insulation box.

10. Use of the foam insulation box according to claim 9 in the field of heat insulation packaging.

Citation Information

Patent Citations

  • Hollow microsphere reinforced polylactic acid (PLA)-based composite foaming material and preparation method thereof

    CN102585465A